A Bilingual's Perspective on Polysemous and Single Meaning Slogans. Issue 4 (1st October 2016) - Zúñiga, Miguel A.; Torres, Ivonne M.; Niculescu, Mihai
Abstract : Multiculturalism, bilingualism, consumer diversity and predominance of polysemous slogans has increased the complexity of consumer and advertiser interactions. Ad research considering the subjective feelings of ease-of-processing in ad evaluations is limited. Strategically, fluency has the persuasive capacity to impact Aad /Abrand despite consumers' cultural differences and slogan type differences. In the case of single meaning slogans, comprehension played a limited role, therefore, advertisers might diminish the use of comprehension advertising strategies to influence both monolinguals and bilinguals. In the case of polysemous slogans, advertisers should consider that monolingual (vs. bilingual) consumers were impacted more by comprehension when forming Aad /Abrand .